About Latvian Books Printed Outside Latvia - Ernesta Kazakėnaitė (Knygotyra)
The National Library of Latvia has recently published a substantial (479-page) 'Book for Latvia outside Latvia' (Zanders, Viesturs (red.). Grāmata Latvijai ārpus Latvijas: kolektīvā monogrāfija = Books for Latvia outside Latvia: collective monograph. Rīga: Latvijas Nacionālā bibliotēka, 2021. 479 P. ISSN 978-9934-610-05-9.). This collection deserves a special attention, as it begins to fill the gap in systematic research on Latvian publications published abroad. The collection consists of 12 scientific articles on the publication of Latvian books abroad from the 13th to the late 20th century. All the articles are in Latvian, but the table of contents, abstracts and a translation of the first article are also available in English. In this review, the author will discuss the structure and main features of the book.